Transmission of cyber risk through the Canadian wholesale payments system - Anneke Kosse; Zhentong Lu (Bank of Canada, 2022)
In this paper, we study how the impact of a cyber-attack that paralyzes one or multiple banks' ability to send payments would transmit to other banks through the Canadian wholesale payments system. Based on historical payment data, we simulate a wide range of scenarios and evaluate the total payment disruption in the system. We find that depending on the type and number of banks under attack, the time of the attack and the design of the payments system, the attack can quickly become systemic and result in a significant loss of liquidity in the system. For instance, a three-hour attack on one bank can in the worst case impair the payments capacity of seven other banks within less than an hour and eventually disrupt 25% of the daily payments value. We also demonstrate that the system-wide impact of an attack can be significantly reduced by contingency plans that enable attacked banks to still send high-value payments. Given the interconnectedness of banks, we conclude that the cyber-resilience of a wholesale payment system strongly depends on the cyber-resilience of its participants and underline the importance of strong sectoral collaboration and coordination.
Keywords: C49; E4; E42; E47; G2; G21; 330; Payment clearing and settlement systems; Financial institutions; Financial stability